Alternatives for Allergens in the 2018 American Contact Dermatitis Society Core Series: Report by the American Contact Alternatives Group. Issue 2 (March 2019) - Scheman, Andrew; Hylwa-Deufel, Sara; Jacob, Sharon E.; Katta, Rajani; Nedorost, Susan; Warshaw, Erin; Eifrid, Kathryn; Geiser, Andrew J.; McGaughey, Lauren; Scheman, Nicole; Kimyon, Rebecca; Rundle, Chandler; et al.
Abstract : The most successful treatment for contact allergy is allergen avoidance. Patient improvement ultimately relies on identification of safe alternative products, which can be used by the patient. "Safe" personal care product options can typically be found using ingredient database programs. Avoidance of allergens in other products (ie, shoes, clothing, dental care, etc) is often challenging. In this article, the American Contact Alternatives Group discusses how to find specific safe alternatives for the 80 allergens on the American Contact Dermatitis Society core allergen series ( Dermatitis . 2017;28:141–143). The alternatives listed in this article are accurate as of the date of publication; however, the availability of these alternatives may change in the future (disclaimer).